Stolen dreams : portraits of working children - Parker, David L. (David Lewis), 1951-; Engfer, Lee, 1963-; Conrow, Robert, 1942- (Minneapolis : Lerner Publications Co., 1998)
Photographs and text document working children especially in Nepal, India, Bangladesh, and Mexico. Includes a chapter on Iqbal Masih, the child labor activist from Pakistan.
Includes bibliographical references (p. 106-109) and index.
Keywords: Child labor -- Juvenile literature; Child labor -- Case studies -- Juvenile literature; Child labor